A laboratory setup for measuring the wood-surface temperature during drying by means of thermography. Issue 2 (4th March 2023) - Lerman, Peter; Scheepers, Gerhard; Wiberg, Pär
ABSTRACT: The surface temperature of a drying wooden board is strongly related to the drying process. However, it is relatively difficult to determine the surface temperature accurately during drying. In this paper, an experimental setup for analyzing the wood surface during drying by thermal imaging as well as dry and wet-bulb temperature reference surfaces was tested. Spruce sapwood samples were dried in various climates and evaluated with respect to both mass loss and surface temperature. The experimental setup enabled both qualitative and quantitative analysis of the wood drying process. The results showed that thermal imaging enabled a detailed view of the drying progression. The distinct correlation between surface temperature and mass change showed that an accurate determination of a basic, often considered, and difficult-to-determine drying potential is possible.